2015
DOI: 10.1309/ajcpjs4eem7uaubv
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Educational Intervention on the Frequency of Daily Blood Test Orders for Hospitalized Patients

Abstract: Provider education and reminders can reduce the frequency of daily blood tests ordered by providers for hospitalized patients. This can decrease health care costs and may reduce the risk of complications such as anemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…Many of these focused on order entry process, either through alterations in the ordering process [16][17][18][19][20][21] or providing charge data in electronic ordering systems. 23,24 Although feedback to teams regarding charges 25 and educational initiatives 30 have decreased costs, we believe our report is the first to use improvement science to combine multiple interventions that have successfully improved and sustained physician ordering behavior without a technology support emphasis.…”
Section: Resultsmentioning
confidence: 91%
“…Many of these focused on order entry process, either through alterations in the ordering process [16][17][18][19][20][21] or providing charge data in electronic ordering systems. 23,24 Although feedback to teams regarding charges 25 and educational initiatives 30 have decreased costs, we believe our report is the first to use improvement science to combine multiple interventions that have successfully improved and sustained physician ordering behavior without a technology support emphasis.…”
Section: Resultsmentioning
confidence: 91%
“…Many interventions are multifaceted incorporating both a component of person‐oriented intervention as well as change in system design or process. Table lists the studies reviewed that have used education and reminders, audit and feedback, computer physician entry order systems, and forcing restraints …”
Section: Improving Test Utilizationmentioning
confidence: 99%
“…Other studies have shown short‐term benefits. Thakkar et al performed an educational session, with educational flyers and weekly email reminders, whereas Ko et al performed an educational session, followed by visual reminders throughout the surgical intensive care unit (SICU) and a daily checklist. Both saw a significant decrease overall in blood tests ordered and associated cost savings without a change in mortality during the intervention period.…”
Section: Educational Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the effect of reducing the frequency of laboratory testing on clinical outcomes, such as rate of complications or hospital length of stay, is difficult to determine due to the number of confounding factors. Most studies in this area assumed clinical equivalence rather than tracking outcomes …”
Section: Discussionmentioning
confidence: 99%